Faktor Internal Terhadap Kinerja Keuangan Pada Perusahaan Sektor Barang Food & Beverage - Daniel Daniel; Hermanto Hermanto (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to analyze the influence of internal company factors, including company size, networking capital, operating efficiency, liquidity, and leverage, on financial performance, proxied by Return on Assets. The research population includes 40 food & beverage subsector companies listed on the Indonesia Stock Exchange during the 2019–2024 period. Using purposive sampling, 17 sample companies were selected, yielding a total of 102 data observations. This study adopts a quantitative approach, using secondary data obtained from the company's annual financial statements. Data analysis was performed using multiple linear regression to identify partial and simultaneous influences between variables. Empirical findings show that not all internal factors exert a uniform influence on financial performance, as some variables have been shown to have a significant influence, while others do not show a statistically significant relationship. These results have important implications for managers and investors in formulating internal management strategies to drive sustainable profitability